A study on factors influencing the national carbon emission trading price in China - Mingzhu Liao; Feng Long; Xue Tian; Fenfen Bi; Wei Tian; Xiao Li; Chazhong Ge (PLoS ONE, 2025)
On 16 July 2021, China officially launched its national carbon emissions trading market, which has since become the largest market in the world in terms of coverage of greenhouse gas emissions and plays an important role in combating global climate change. This study selects the national carbon emissions trading price data from July 16, 2021 to August 31, 2024, which records the price fluctuation characteristics in the early stage of the market (covering only the stage of the electric power industry), which not only provides a historical reference for the subsequent inclusion of the industry, but also provides an important basis for evaluating the effectiveness of the market construction and the optimization of the policy. At the same time, the VEC model is used to study the dynamic relationship between the national carbon emission trading price and key variables, including energy prices, macroeconomic conditions, the development of the power industry, international carbon prices, carbon emissions from the power industry, and the trading volume of national carbon emission quotas. The results show that there is a long-term equilibrium relationship between the national carbon trading price and the variables, which provides a scientific basis for setting a reasonable fluctuation range of the carbon price. Furthermore, impulse response and variance decomposition analyses were conducted to evaluate the short-term dynamic effects of each variable on the national carbon emission trading price. The results reveal that the trading volume of national carbon emission quotas and the development of the power industry exert significant influence on the national carbon emission trading price. In addition, the carbon emissions of the electric power industry have a positive impact on the national carbon emissions trading price in the short-term situation, and in the long-term situation, they have a negative impact. This provides a parameter calibration basis for the expansion of the industry and a reference for policy making, which is important for the construction of the national carbon emission trading market with international influence. The marginal contributions of this study are:(1) forming a new combination of variables for a comprehensive analysis of the national carbon emissions trading market; (2) the empirical results uncover new insights into the dynamics of the national carbon price; and (3) providing empirical evidence for improving the institutional system of the national carbon emissions trading market.